Charge Carrier Dynamics of Polymer:Fullerene Blends: From Geminate to Non‐Geminate Recombination. Issue 8 (8th February 2014) - Vithanage, Dimali Amarasinghe; Wang, Ergang; Wang, Zhongqiang; Ma, Fei; Inganäs, Olle; Andersson, Mats R.; Yartsev, Arkady; Sundström, Villy; Pascher, Torbjörn
<x xml:space="preserve">Abstract</x> The charge carrier dynamics of a new polymer‐fullerene blend are examined on the femtosecond to the millisecond time scale. The full time range is globally fitted using a chemical reaction rate model that includes all key processes, charge generation, energy transfer, charge separation, and recombination, over the full 12 orders of magnitude in time and a factor of 33 in light intensity. Particular attention is paid to the charge recombination processes and it is found that they are highly material specific. Comparison of the dynamics to those of a previously studied polymer:fullerene blend reveals that while for one blend the recombination dynamics are mainly controlled by geminate recombination, the charge recombination in the presently studied polymer:fullerene blend are entirely controlled by non‐geminate electron‐hole recombination. Carrier density dependence of the non‐geminate recombination rate is analyzed and a correlated disorder model of site energies is proposed to explain the observed dependency.